Impact of low-carbohydrate diet on health status: an umbrella review - Alkhunein, Sarah; Alawad, Rehab; Alhumaidan, Omar; Fatani, Bushra; Alolayan, Abeer; Alfelyeh, Tarfah; Alakeel, Shihana; Almuhtadi, Yara (Frontiers in Nutrition, 2024)
Dear Editor of Frontiers Journal, I'm submitting to Frontiers in Nutrition Journal a manuscript "Impact of Low-Carbohydrate Diet on Health Status: An Umbrella Review" for consideration. I acknowledge that the accompanying article is original and not being submitted to other publications. To the best of our current understanding, prior endeavours in umbrella reviews have primarily concentrated on evaluating either one specific type of low-carbohydrate carbohydrate diets (LCDs) or the meta-analyses of observational data that were incorporated. Therefore, the primary objective of this umbrella review was to conduct a systematic evaluation of previously conducted meta-analyses and systematic reviews that have examined the effects of LCDs on various health conditions. The aim was to gain a better understanding of the potential effectiveness of LCDs, summarize the findings of these studies, and assess the overall strength of evidence to provide a comprehensive perspective. This article holds significant value for future research as it identified the gap in the current literature, also, it can provide valuable assistance to dietitians, nutritionists, and researchers in assessing the relative effectiveness of LCDs on various health outcomes. Thank you very much for your time and consideration. Yours Sincerely, Ms. Rehab